Gambaran Self-Management Pada Pasien Stroke Yang Menjalani Rawat Jalan - Rahmawati, Dedah; Kurniawan, Titis; Hartati, Sri (Jurnal Keperawatan 'Aisyiyah, 2019)
Stroke patients require a long-term treatment, both to prevent recurrent stroke and to minimize further complications. One of the efforts to succeed the stroke patients' treatment is Self-Management. This study aimed to identify the self-management of stroke outpatients. This quantitative descriptive study involved 40 stroke outpatients in RSAI who are able to communicate well, taken by using consecutive sampling techniques for one week. The data were collected by using a Stroke Self-Management Questionnaire (SSMQ) consisting of 4 domains (capacity, confidence in interaction, strategy, and guidance by health professionals). The collected data were analyzed descriptively by using the mean value. The result showed that the percentage of respondents with high self-management category (52,5%) was higher than the low category. Furthermore, the percentage of the good category was higher in the domain of confidence in interaction, strategy (52.5%), as well as guidance by health professionals (55%). Meanwhile, the percentage of the low category was found higher in the domain of capacity (52.5%). Keywords: Self-Management, Stroke